2007
DOI: 10.1007/s10565-007-9003-4
|View full text |Cite
|
Sign up to set email alerts
|

Vanadate-induced cell death is dissociated from H2O2 generation

Abstract: Vanadium is an environmentally toxic metal with peculiar and sometimes contradictory cellular effects. It is insulin-mimetic, it can either stimulate cell growth or induce cell death, and it has both mutagenic and antineoplastic properties. However, the mechanisms involved in those effects are poorly understood. Several studies suggest that H(2)O(2) is involved in vanadate-induced cell death, but it is not known whether cellular sensitivity to vanadate is indeed related to H(2)O(2) generation. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 52 publications
0
28
0
2
Order By: Relevance
“…Stock solutions of genistein (50 mM) and M (100 mM) were prepared in DMSO and stored at −20°C. SO stock solution was prepared in distilled sterile water (1 mM, pH 10) according to previous study guidelines [32,38] and stored at −80°C. Final dilutions of the investigated drugs were prepared in cell culture media prior to use.…”
Section: Investigated Agents and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stock solutions of genistein (50 mM) and M (100 mM) were prepared in DMSO and stored at −20°C. SO stock solution was prepared in distilled sterile water (1 mM, pH 10) according to previous study guidelines [32,38] and stored at −80°C. Final dilutions of the investigated drugs were prepared in cell culture media prior to use.…”
Section: Investigated Agents and Reagentsmentioning
confidence: 99%
“…They also exhibit antineoplastic activity against multidrug-resistant tumor cells [31]. The particular cytotoxic mechanism of action for vanadium salts has not been elucidated, but several possibilities, such as inhibition of protein phosphatases, protein kinases involvement, DNA damage, changes in cytosolic calcium, generation of ROS and oxidative stress, have been proposed [30,32]. On the other hand, vanadium salts as dietary microelements [30] have high biological significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies suggested a close relationship between vanadium toxicity and ROS [9,[20][21][22]. Vanadium induced apoptosis of cells associated with elevated ROS levels and ROS-related signal transduction [23,24], while antioxidants, either as complex ligands [25] or co-administration [26,27], significantly reduced vanadium toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that vanadate induced cell cycle arrest at the G2/M phase by H 2 O 2 -activated ERK and p38 pathways (Zhang et al 2003). But, there might be another mechanism leading to vanadate-induced cytotoxicity independent on H 2 O 2 generation (Capella et al 2002(Capella et al , 2007. Our group also demonstrated that vanadate can induce cell cycle arrest in HepG2 cells via an ROS-independent pathway (Fu et al 2008), and by using antioxidants as synergistic agents, the damage to normal liver cells may be avoided (Wang et al 2010).…”
Section: Discussionmentioning
confidence: 99%